MORPHOLOGICAL CHALLENGES FOR UZBEK LEARNERS OF ENGLISH: A COMPARATIVE LINGUISTIC STUDY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Morphology, the study of word formation, is essential for language learners as it helps them understand how different morphemes (the smallest units of meaning) combine to create words. Morphological awareness plays a significant role in building vocabulary and constructing sentences, particularly in English, a language with complex morphemes and frequent exceptions. For Uzbek learners of English, morphology presents unique challenges due to structural differences between Uzbek and English. This article examines key areas of morphological difficulty for Uzbek learners and explores strategies for addressing these challenges in the classroom.